Working time distribution and administrative burden in Austrian community health nursing: A cross-sectional survey - Raimund M. Kovacevic; Doris A. Behrens; Walter Hyll (International Journal of Nursing Studies Advances, 2025)
Background: Community health nursing was introduced in Austria in 2022. As the 117 pilot projects now transition into centrally managed services, data on nurses’ working time distribution and client contact patterns are essential for workforce and location planning to ensure optimal service delivery. Objective: To analyse the working time distribution and client contact patterns of Austrian community health nurses during the pilot phase (2022–2024). Design: Cross-sectional survey. Setting(s): An online survey (April to June 2023) among community health nurses captured their working time distribution and client contact patterns. Participants: Out of the N = 220 eligible community health nurses, 121 (55%) nurses answered the questions relevant to working time analysis and 115 (52%) for studying regional disparity of service delivery. Methods: The analysis used descriptive statistics, statistical tests, and regression analysis, employing Excel®, Stata® and R. Results: Our analysis shows that 92% of the community health nurses in Austria work in non-urban areas. On average, they have one client contact every five working hours, lasting around 75 minutes. Seventy per cent of these encounters result in follow-ups, usually within ten days. Across all regions, 28% of the Austrian community health nurses’ working time is dedicated to home visits and in-office consultations, 7% to outreach efforts aimed at attracting new clients, and 6% to travelling. Further, 29% of time is spent on administration and project management, 8% on team meetings, and 20% on networking and public relations. Service delivery varies significantly by region: rural nurses report fewer consultation hours and more time spent on travelling. Regardless of geography, the time spent on organisational tasks increases disproportionately—and more than any other activity—as total working hours increase. Conclusions: Each hour spent with a client requires an hour of administration, with no observable efficiency gains in administrative tasks as working hours increase. These findings highlight the need to explore whether targeted organisational support, such as administrative assistance or digital documentation tools, may improve efficiency. Additionally, current restrictions on client outreach and age eligibility may unnecessarily hinder service effectiveness and accessibility. Tweetable abstract: Study of Austrian community health nurses reveals: for every hour with clients, nurses spend an equal hour on administration. Administrative burden grows disproportionately with longer working hours, with no efficiency gains.